Simple model for the thermal conductivity estimation on the basis of Raman and ESR spectroscopy measurements - Masierak, Włodzimierz; Fabisiak, Kazimierz; Kaczmarski, Marceli; Kozanecki, Marcin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The diamond films were grown at different working gas pressure in the range of 20–80 mbar by using hot filament chemical vapor deposition (HF CVD) technique. It was observed that the film morphology was dependent on deposition pressure and changed from so called “ball-like” via (111) and (100) type to the morphology of mixed character. The diamond film quality was studied by means of Raman and ESR (electron spin resonance) spectroscopy measurements. Within the presented work a simplified model for heat conductivity was proposed which allows to estimate the value of the thermal conductivity on the basis of Raman and ESR measurements. The obtained results are in good agreement with those reported in literature.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 225-234
Keywords: optyka; diamond film; chemical vapor deposition (CVD); Raman spectroscopy; electron spin resonance (ESR); thermal conductivity